Altered Peripheral Immune Profiles in First-Episode, Drug-Free Patients With Schizophrenia: Response to Antipsychotic Medications - Chen, Lei; Zheng, Wen-Hui; Du, Yang; Li, Xue-Song; Yu, Yun; Wang, Hua; Cheng, Yong (Frontiers in Medicine, 2021)
Previous research has demonstrated aberrations in the levels of inflammatory cytokines in patients with schizophrenia (SCZ), but most of the respective studies have tested a narrow set of inflammatory cytokines. Here, we aimed to analyze broad immune profiles in the peripheral blood of the first-episode drug-free (FEDF) patients with SCZ at baseline and after an 8-week treatment with atypical antipsychotics. Serum samples from 24 FEDF patients with SCZ and 25 healthy control (HC) subjects were tested using Luminex multiplex analysis for 30 cytokines, chemokines, and growth factors. Multiple comparison tests demonstrated that interleukin-2 (IL-2), IL-4, interferon-gamma (IFN-γ), monokine induced by IFN-γ, and granulocyte colony-stimulating factor (G-CSF) levels were significantly increased, whereas those of the epidermal growth factor were significantly decreased in the FEDF patients with SCZ. Moreover, the levels of the 6 dysregulated cytokines as well as those of 12 additional soluble factors in FEDF patients with SCZ were significantly decreased after 8 weeks of antipsychotic treatment. Furthermore, the transcription of G-CSF and IFN-γ was significantly increased in FEDF patients with SCZ when compared with controls, and G-CSF and IFN-γ mRNA levels were highly correlated with their respective protein concentrations. Receiver operating characteristic curves showed that G-CSF and IFN-γ had good performance in differentiating between FEDF patients with SCZ and HC subjects. Taken together, our data revealed that FEDF patients with SCZ were accompanied by a unique pattern of immune profile, and antipsychotic medications seemed to suppress the immune function in these patients, which could be used to develop novel targets for the diagnosis and treatment of SCZ.